Isolation of a novel bioactive protein from an edible mushroom Pleurotus eryngii and its anti-inflammatory potential. Issue 6 (19th May 2017) - Yuan, Biao; Zhao, Liyan; Rakariyatham, Kanyasiri; Han, Yanhui; Gao, Zili; Muinde Kimatu, Benard; Hu, Qiuhui; Xiao, Hang
Abstract : A novel protein with anti-inflammatory effects was isolated from Pleurotus eryngii . Abstract : Edible mushrooms are rich sources of bioactive components. In this study, a bioactive protein, PEP, was isolated from an edible mushroom, Pleurotus eryngii, through (NH4 )2 SO4 precipitation and ion-exchange chromatography. Proteomic analysis by matrix assisted laser desorption ionization-time of flight mass spectrometry showed that PEP was a novel protein with a molecular weight of 40 kDa. PEP exhibited anti-inflammatory effects in LPS-stimulated RAW 264.7 macrophages by inhibiting the overproduction of pro-inflammatory mediators including nitric oxide (NO), cytokine IL-1β and IL-6. It was further demonstrated that these anti-inflammatory effects of PEP were associated with the inhibition of inducible nitric oxide synthase (iNOS) expression, and the deactivation of nuclear factor-kappaB (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. Our results demonstrated that PEP might be a good candidate for anti-inflammation in the gastrointestinal tract, especially in the colon.